PEMANFAATAN BAGIAN PUTIH KULIT SEMANGKA SEBAGAI BAHAN TAMBAHAN CAKE PUDDING - Gloria Blessing Gosal Manopo; Astrid, Astrid; Aurlicia Liando; Johannes Kurniawan; Stephanie T. Mulyono (LPSDI Bina Patria, 2025)
Cake Pudding is an innovation that combines two elements, namely cake and pudding. Researchers created the latest dessert innovation with a soft and layered texture. Watermelon rind is used as a dessert that has a unique taste. Watermelon rinds are a research topic on how to use something that is often thrown away and ignored by society even though it can be processed into food. Watermelon rind contains very important nutrients such as fiber, citrulline and antioxidants which function to increase the nutritional content of the product. It is hoped that the use of watermelon rind in cake pudding can reduce food waste, which is the largest contributor to organic waste in Indonesia. Through this cake pudding research, it is hoped that an attractive and sustainable healthy food alternative will be created in the food industry by contributing to reducing food waste